The Organisational Engagement of Employees as a Source of Participation in the Organisation - Adamska-Chudzińska, Małgorzata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The article reviews the concepts of organisational engagement from a historical perspective. It emphasises a diversity of approaches and the particular achievements in separate periods. A model of organisational engagement proposed by Mayer and Allen was chosen as best representing the basic trend of contemporary research on engagement. Their model includes differentiation of three independent components of organisational engagement – emotional, rational and normative. Each of them is connected with a different mental state, and a corresponding behaviour at work. Hence, it is possible to suggest three main justifications of participation in an organisation (willingness, necessity and duty) and thus there is a connection between those causes of behaviour and the type of engagement that occurs within it. The author stresses that the majority of scholars agree that the emotional aspect of engagement is key in producing authentic and strong identification with an organisation.